Federalism, Continentalism and Economic Development in Canada - Armstrong, Christopher (Czasopismo Prawno-Historyczne, 1980)
Canada is a huge country of diverse regions, sparsely populated but richly endowed with natural resources. Of its ten provinces all except Nova Scotia and the two islands, Newfoundland and Prince Edward Island, possess lengthy borders with the United States of America. Living next to the world's largest and most dynamic industrial economy has had a significant impact not only upon the nation's economic development but upon its federal system. By the Canadian constitution the provinces control "all lands, mines, minerals and royalties belonging to the several Provinces […] at the Union", along with "the management and sale of the Public Lands belonging to the province[s] and of the timber and wood thereon". This jurisdiction gives the provinces very extensive powers to manage the development of their natural resources, resources for which a ready market has developed in the United States since the turn of the century.